Effect of foliar application on potato yield - Rajendra Bhatt; Manoj Raghav; S B Bhardwaj; Lalit Bhatt; Yashpal Singh Bisht; Mukesh Kumar (Current Horticulture, 2025)
A study was carried out to explore the response of foliar nutrients on economic yield and tuber quality of potato (Solanum tuberosum L., cv. Kufri Surya) at GBPUA&T, Pantnagar, Uttarakhand, during rabi season of 2017-18. The experiment had eleven treatments replicated four times. Among all treatments, based on overall performance treatment T11 (75% N of RDF as basal + 2% foliar spray of 20:20:20 water-a soluble fertilizer at 30 and 45 DAP) was found best concerning marketable yield (36.71 t/ha), dry-matter content of tubers (20.42%), protein content in tubers (8.05%), specific gravity of tubers (1.11 g cc-1) and benefit:cost ratio (1.96). It is concluded that foliar application of nutrients had a notable impact on both yield and quality of potato tubers.